1997
DOI: 10.1038/385093a0
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory intramolecular association in a tyrosine kinase of the Tec family

Abstract: The T-cell-specific tyrosine kinase Itk is a member of the Tec family of non-receptor tyrosine kinases, and is required for signalling through the T-cell antigen receptor (TCR). The role of Itk in TCR signalling and the manner in which Itk activity is regulated are not well understood. Substrate binding and enzymatic activity of the structurally related Src kinases are regulated by an intramolecular interaction between the Src-homology-2 (SH2) domain and a phosphotyrosine. Although Itk also contains SH3, SH2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
223
1
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(237 citation statements)
references
References 26 publications
11
223
1
2
Order By: Relevance
“…We therefore disrupted the integrity of each of these domains to determine whether they were required for this dimerization. The PRR within the unique TH domain of Itk has been suggested to interact with the SH3 domain of Itk in an intramolecular interaction (31). However, we found that Itk mutants carrying a deletion in the PRR of the TH domain could still form dimers with the WT Itk (Fig.…”
Section: Resultscontrasting
confidence: 47%
“…We therefore disrupted the integrity of each of these domains to determine whether they were required for this dimerization. The PRR within the unique TH domain of Itk has been suggested to interact with the SH3 domain of Itk in an intramolecular interaction (31). However, we found that Itk mutants carrying a deletion in the PRR of the TH domain could still form dimers with the WT Itk (Fig.…”
Section: Resultscontrasting
confidence: 47%
“…However, the results of the genome sequencing of Saccharomyces cerivisiae suggest that this organism has only 25 genes that encode for SH3-domain containing proteins (Rubin et al, 2000). Moreover, many SH3 interactions, especially those mediating intramolecular protein ± protein interactions, serve to negatively regulate signal transduction (Franz et al, 1989;Jackson and Baltimore, 1989;Seidel-Dugan et al, 1992;Mayer and Baltimore, 1994;Yamashita et al, 1996;Andreotti et al, 1997;reviewed in Mano, 1999;Kay et al, 2000). Taken together, the current studies suggest that, at least in yeast, SH3-mediated protein ± protein interaction may be dispensable for the viability of the organism.…”
Section: Discussionmentioning
confidence: 60%
“…In engagement of integrin, the PH domain of Etk is recruited to the FERM domain of focal adhesion kinase, leading to phosphorylation of Tyr-40, concomitant with the membrane translocation and unfolding the closed conformation of the inactive Etk. Membrane-targeting of Etk will allow Etk to be phosphorylated by Src family kinases at the highly conserved tyrosine residue Tyr-566 in the catalytic domain (29), which is originally masked by the PH domain (38). In TNF signaling, Etk forms a preexisting complex with TNFR2 located in the cytoplasm membrane in a closed inactive form.…”
Section: Discussionmentioning
confidence: 99%